Arrangements for Granting Visas and Immigration Stay Permits for Digital Nomads in Indonesia in View of Legal Certainty: Pengaturan Pemberian Visa dan Izin Tinggal Keimigrasian bagi Digital Nomad di Indonesia Ditinjau dari Kepastian Hukum - Imam, Lalu Syamsul; Wibowo, Gatot Dwi Hendro; Cahyowati, Cahyowati (Indonesian Journal of Law and Economics Review, 2024)
In the era of globalization, Indonesia stands to gain substantial benefits by swiftly implementing regulations governing visas and residence permits for digital nomads, ensuring legal certainty and unlocking significant economic potential. This research employs a normative legal approach to analyze the concept of specialized visa and residence permit arrangements for digital nomads in Indonesia, focusing on legal certainty and the classification of their activities as work. Current findings indicate a lack of specific rules for digital nomads, leading to the use of conventional visas that may not align with their online work. As digital nomads inherently engage in freelance work, compliance with labor and taxation regulations becomes imperative. To establish lawful and protected status, the government should introduce new arrangements, such as digital nomad visas with stipulated requirements like financial capability and tax payments, fostering legal certainty for all stakeholders. Highlights: Legal Void: The absence of specific rules for digital nomads in Indonesia leaves them reliant on conventional visas, creating a legal vacuum for their online work activities. Freelance Work Classification: Given that digital nomads essentially function as freelance workers, the research emphasizes the necessity of appropriately categorizing their activities within the framework of labor and taxation regulations. Policy Recommendations: The study advocates for the prompt establishment of specialized digital nomad visas and residence permits in Indonesia, incorporating financial criteria and tax obligations to ensure legal certainty and unlock economic potential. Keywords: Digital Nomads, Visa Regulations, Legal Certainty, Economic Potential, Indonesia